CELL WALL POTENTIAL IN NITELLA - NAGAI, REIKO; KISHIMOTO, UICHIRO (Oxford University Press, 1964)
In the process of inserting a microelectrode into the vacuole of Nitella three potential levels were recorded. The first one was at a water phase outside the cell wall, the second one in the cell wall and the third one across the plasmalemma. The first potential was variable with the distance from the surface of the cell wall. When the external solution was 10−4 M KCl, the second potential level was −90 mv and the third one −170 mv against an external reference electrode. These potentials were less negative (more negative) with the increase (decrease) of the external KCl concentration and varied to some extent among samples. The vacuolar potential measured against the cell wall phase was, therefore, −80 mv inside negative to outside. A large potential change such as action potential was observed only across the plasmalemma. An overshoot of the action potential of Nitella flexilis was observed very often, when the vacuolar potential was measured against the cell wall phase.